Factors that influenced leadership behavior based on gender / Noel Clsyter Philip - Philip, Noel Clsyter (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2009)
The purpose of this study is seeing the factor that might influenced the leadership behavior based on gender among workers in government and private sector in Kofa Kinabalu area. There are 100 respondents that have been chosen randomly to participate in this study. The research objectives are to identify if there is any differences between male and female leadership behavior and the factor that might influenced the behavior.